Studi Perbandingan Hukum Negara Indonesia dengan Negara Filipina Tentang Pengaturan Pertanggung Jawaban Pidana Anak (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This research aims to provide a comprehensive analysis of the structure of child criminal liability in Indonesia and the Philippines, as well as to ascertain the specific nature of child criminal liability in both countries. This study is a prescriptive normative legal research. The research methodologies employed include the legal approach, the comparison approach, and the conceptual approach. The legal resources used can be classified into primary and secondary sources. To ensure the acquisition of precise primary and secondary data for this paper, data gathering is conducted through a thorough examination of relevant literature pertaining to the principles and regulations governing the child criminal justice system. This research focuses on comparing the legislation of child criminal culpability in Indonesia and the Philippines. The child criminal justice system is governed by specific legislation. In the State of Indonesia, it is managed by the Child Criminal Justice System Act, while in the Philippines, it is regulated by Republic Act No. 9344, with revisions made by Republic Act No. 10630. In Indonesia, the age at which a kid can be held criminally liable is between 12 and less than 18 years old. In the Philippines, children can be held criminally liable starting at the age of at least 15 years old and up to less than 18 years old. In the Philippines, there is a kind of criminal culpability that results in automatic suspension, removal from position, probation, and the application of vicarious liability for parents. Child criminal culpability in Indonesia is determined based on individual responsibility, as stated in Article 71 of the Child Criminal Justice System Law. This law specifies the application of criminal sanctions. Additionally, Article 82 of the same law outlines the imposition of action punishments.